ADAT LAMPUNG PEPADUN DALAM TINJAUAN FILSAFAT HUKUM ALAM (Lampungnese Tradition of Papaduan in the Review of Philosophy of Natural Law) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRAC The present thesis critically review custom and tradition of Lampungnese named Pepadun to know its real values of relevancy and con¬tribution to development of nasional law and functions of the values for the development policies in autonomy at Lampung terrtory. The study is a literture study where this formal object is a naturl law philosophy of Middle Age and the twentieth century. Methodology used to reveal the custom es¬sence or custom law of Lampungnese named Pepdun, that is a hermeneutics and reflective method with a philosophical approach. With the method and approach the problem and answering dialectics can be interpreted for the parts and elements completely in the custom and tradition laaw such as the origin, foundation, nature, its functions and goals in order getting to know 'truthfully what being the custom law essence of Lampungnese named Pepadun. After doing the research it can be found that the real values being the custom essence or Lampungnese custom low of Pepadun is the deity values emanated into the human reality. The human reality derives human values among them comprising togetherness values, similarity, justice, family atmo¬sphere and sacrificing. The custom low values of Lampungnese named Pepadun philosophically is very relevant to Pancasila values being the source and national low foundation. The contribution of custom low values of Lampungnese named Pepadun is in the national low development, where the deity values and humanity must be placed as the foundation and law sources and other policies consequently, including the development policies in the era of territorial autonomy especially in the territory of Lampung so the na¬tional law and development in regional autonomy will take side with the humanity that can be manifested concretely in the entirely of Indonesian Archipelago, specifically in the land of Sang Bumi Ruwa Jurai.